SISTEM INFORMASI APLIKASI INVENTORY STOK BARANG BERBASIS DEKSTOP MENGGUNAKAN METODE EXTREME PROGRAMMING STUDI KASUS : HURIAH TEMBAKAU - Ahmad Fadly Fahmi; Muhamad Fahrezi; Nur Muhammad Fikri; Roeslan Djutalov (Shofanah Media Berkah, 2023)
This research aims to design a desktop-based stock inventory information system using the Extreme Programming method for Huriah Tobacco company. This company currently still relies on manual records in managing inventory, which causes a lack of effectiveness and efficiency in checking stock. In this research, the author will identify weaknesses in the current system, design appropriate solutions, and implement the designed information system. The Extreme Programming method is used to accelerate and adapt the system development process according to company needs. It is expected that with the implementation of this information system, Huriah Tembakau will be able to improve company performance and optimize inventory management.